Analisis Konflik Peran antara Aktivitas Akademik dan Organisasi serta Dampaknya terhadap Pengembangan Diri Mahasiswa PGSD - Lia Rahayu; Jesi Alexander Alim; Zakiah Ulya (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to analyze the role conflict experienced by PGSD (Elementary School Teacher Education) students at the University of Riau between academic and organizational activities, as well as to examine its impact on students’ self-development. This research employed a descriptive quantitative approach involving 30 active students engaged in both academic and student organization activities. Data were collected through a Likert-scale questionnaire based on three dimensions of role conflict proposed by Greenhaus and Beutell (1985): time-based, strain-based, and behavior-based conflicts. The results show that the level of role conflict among PGSD students is categorized as moderate, with an average score of 64.61. This indicates that most students are able to balance academic and organizational roles, although they face challenges in time management and role pressure. Furthermore, role conflict contributes positively to self-development, as students enhance their time management, responsibility, leadership, and communication skills. Therefore, role conflict can serve as a learning medium if managed adaptively. This study recommends that universities provide training in time management and organizational guidance to help students achieve a balanced integration between academic and extracurricular commitments.